Ritual Pengobatan Maduai Kaka’ pada Suku Bajo di Desa Langara Bajo Kecamatan Wawonii Barat Kabupaten Konawe Kepulauan - Firmayanti Firmayanti; Syahrun Syahrun; Rahmat Sewa Suraya (LISANI: Jurnal Kelisanan, Sastra, dan Budaya, 2024)
The Maduai Kaka' Treatment Ritual is a ritual performed by the Bajo Tribe Community in Langara Bajo Village, West Wawonii District, Konawe Islands Regency. Inheritance pattern of the Maduai Kaka' Medicine Ritual in Langara Bajo Village, West Wawonii District, Konawe Islands Regency. The research method used in this research is descriptive qualitative. Data collection was carried out by observation, interview and documentation techniques. The technique of determining informants used purposive techniques, the data were analyzed using data collection techniques, data reduction, data presentation, and drawing conclusions.The results showed that the process of carrying out the Maduai Kaka' Treatment Ritual consisted of several stages, (1) the stage of disease diagnosis, this stage was the stage of examining the disease, (2) the stage of preparing tools and materials, (3) the stage of preparing the preparation of tools and materials this is the stage of preparing the offerings, (4) the stage of carrying out the treatment ritual, finally (5) the final stage of the treatment process. The function of the Maduai Kaka Treatment Ritual for the Bajo tribe in Langara Bajo Village, West Wawonii District, Konawe Islands Regency, namely (1) to maintain traditional ritual patterns (2) for treatment and (3) to reduce expenses. The pattern of inheritance in the Madua Kaka's Treatment Ritual is obtained through traditional leaders, namely sandro/shaman who leads the maduai kaka' treatment ritual, the type of inheritance of Madua Kaka' is enculturation and socialization.